A Generalized Method for High‐Speed Fluorination of Metal Oxides by Spark Plasma Sintering Yields Ta3O7F and TaO2F with High Photocatalytic Activity for Oxygen Evolution from Water. Issue 20 (10th April 2021) - Lange, Martin Alexander; Khan, Ibrahim; Opitz, Phil; Hartmann, Jens; Ashraf, Muhammad; Qurashi, Ahsanulhaq; Prädel, Leon; Panthöfer, Martin; Cossmer, Antje; Pfeifer, Jens; Simon, Fabian; von der Au, Marcus; et al.
Abstract: A general method to carry out the fluorination of metal oxides with poly(tetrafluoroethylene) (PTFE, Teflon) waste by spark plasma sintering (SPS) on a minute scale with Teflon is reported. The potential of this new approach is highlighted by the following results. i) The tantalum oxyfluorides Ta3 O7 F and TaO2 F are obtained from plastic scrap without using toxic or caustic chemicals for fluorination. ii) Short reaction times (minutes rather than days) reduce the process time the energy costs by almost three orders of magnitude. iii) The oxyfluorides Ta3 O7 F and TaO2 F are produced in gram amounts of nanoparticles. Their synthesis can be upscaled to the kg range with industrial sintering equipment. iv) SPS processing changes the catalytic properties: while conventionally prepared Ta3 O7 F and TaO2 F show little catalytic activity, SPS‐prepared Ta3 O7 F and TaO2 F exhibit high activity for photocatalytic oxygen evolution, reaching photoconversion efficiencies up to 24.7% and applied bias to photoconversion values of 0.86%. This study shows that the materials properties are dictated by the processing which poses new challenges to understand and predict the underlying factors. Abstract : Spark plasma sintering (SPS) allows the solid‐state fluorination of Ta2 O5 to TaO2 F and Ta3 O7 F with poly(tetrafluoroethylene) on a minute scale, which reduces the preparation time compared to conventional chemistry by three orders of magnitude. The microstructure of SPS‐prepared TaO2 F and Ta3 O7 F leads to high photocatalytic activity for the oxygen evolution from water, whereas TaO2 F and Ta3 O7 F prepared by conventional chemistry are catalytically almost inactive.